A bone-conducted Tullio phenomenon—A bridge to understand skull vibration induced nystagmus in superior canal dehiscence - Dumas, Georges; Curthoys, Ian S.; Castellucci, Andrea; Dumas, Laurent; Perrin, Philippe; Schmerber, Sébastien (Frontiers in Neurology, 2023)
Nystagmus produced in response to air-conducted sound (ACS) stimulation—the Tullio phenomenon—is well known in patients with a semicircular canal (SCC) dehiscence (SCD). Here we consider the evidence that bone-conducted vibration (BCV) is also an effective stimulus for generating the Tullio phenomenon. We relate the clinical evidence based on clinical data extracted from literature to the recent evidence about the physical mechanism by which BCV may cause this nystagmus and the neural evidence confirming the likely mechanism. The hypothetical physical mechanism by which BCV activates SCC afferent neurons in SCD patients is that traveling waves are generated in the endolymph, initiated at the site of the dehiscence. We contend that the nystagmus and symptoms observed after cranial BCV in SCD patients is a variant of Skull Vibration Induced Nystagmus (SVIN) used to identify unilateral vestibular loss (uVL) with the major difference being that in uVL the nystagmus beats away from the affected ear whereas in Tullio to BCV the nystagmus beats usually toward the affected ear with the SCD. We suggest that the cause of this difference is a cycle-by-cycle activation of SCC afferents from the remaining ear, which are not canceled centrally by simultaneous afferent input from the opposite ear, because of its reduced or absent function in uVL. In the Tullio phenomenon, this cycle-by-cycle neural activation is complemented by fluid streaming and thus cupula deflection caused by the repeated compression of each cycle of the stimuli. In this way, the Tullio phenomenon to BCV is a version of skull vibration-induced nystagmus.